2019
DOI: 10.1002/ar.24211
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Ultrastructure: A Direct Comparison between Conventional Specimen Preparation and High‐Pressure Freezing/Freeze‐Substitution

Abstract: It is generally agreed within the microscopy community that the quality of ultrastructure within the connective tissue matrix resulting from high-pressure freezing followed by freeze-substitution (HPF/FS) far exceeds that gained following the "conventional" preparation method, which includes aqueous fixation, dehydration, and embedding. Exposure to cryogen at high pressure is the only cryopreservation method capable of vitrifying tissue structure to a depth exceeding 200 μm. Cells within connective tissues pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Finally, grids were rinsed in Tris for 15 minutes, then in distilled water for 15 minutes. Sections were evaluated unstained for background and specific labeling, then contrasted for 4 minutes in 4% Uranyl acetate followed by quarter-strength Reynold’s lead citrate for 15 seconds (91).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, grids were rinsed in Tris for 15 minutes, then in distilled water for 15 minutes. Sections were evaluated unstained for background and specific labeling, then contrasted for 4 minutes in 4% Uranyl acetate followed by quarter-strength Reynold’s lead citrate for 15 seconds (91).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, grids were rinsed in Tris for 15 minutes, then in distilled water for 15 minutes. Sections were evaluated unstained for background and specific labeling, then contrasted for 4 minutes in 4% Uranyl acetate followed by quarter-strength Reynold's lead citrate for 15 seconds(72).StatisticsQuantitative experiments were repeated at least three times, reaching similar results. Mean values and standard deviations of all individual specimens from one representative or all independent experiments are presented, as specified in the respective figure legends.…”
mentioning
confidence: 99%
“…Until recently, in traditionally processed tissues for transmission electron microscopy (TEM) (including fixation in glutaraldehyde or formaldehyde) [1] it was considered that the basement membrane (BM) consists of two overlapping well-defined layers: the lamina lucida, a homogeneous structure, clear in electrons flow, and the lamina densa [2], with anchoring filaments, that are extending from the hemidesmosomes (HDs) through the lamina lucida [1]. The preparation techniques by high-pressure freezing (HPF) method and subsequent freeze substitution (FS) can preserve a greater tissue integrity and therefore, it has been found that lamina lucida is actually absent and represents only a fixation artifact.…”
Section: The Basement Membrane and Hemidesmosomes -Recent Findings An...mentioning
confidence: 99%
“…HPF/FS is triumphant in revealing the ultrastructure of smaller organisms; however the successes in cooling exceedingly hydrated tissue ice-crystal free are so rare that biopsies must not be sacrificed to this procedure. Certainly, the few images of well cryo-preserved connective tissue need consideration when deliberating spatial relationships in this difficult tissue (1).…”
mentioning
confidence: 99%